Trans-synaptic modulation of cholinergic circuits tunes opioid reinforcement - Stefano Zucca; Gloria Brunori; Henry A. Dunn; Colten K. Lankford; Laurie P. Sutton; Beatriz Algibez Flores; Nycole A. Maza; Omar Sial; Gogce Crynen; Rafael Luján; Kirill A. Martemyanov (Proceedings of the National Academy of Sciences, 2025)
Opioids trigger structural and functional neural adaptations of the reward circuit that lead to dependence. Synaptic cell adhesion molecules (CAMs) play a pivotal role in circuit organization and present prime candidates for orchestrating remodeling of neural connections in response to drug exposure. However, the contribution of CAMs to opioid-induced rewiring of the reward circuit has not been explored. Here, we used unbiased molecular profiling to identify CAMs in the nucleus accumbens (NAc) modulated by morphine administration. We found that opioid exposure induces the expression of ELFN1, a CAM selectively expressed in cholinergic interneurons in the NAc. We determined that ELFN1 acts trans-synaptically to modulate the strength and plasticity of the glutamatergic inputs onto cholinergic neurons via the recruitment of presynaptic metabotropic glutamate receptor 4 (mGlu4). Disruption of Elfn1 diminished morphine reward and intake in self-administering mice. Together, our findings identify a key molecular factor responsible for adjusting the strength of opioid effects by modulating the configuration of striatal circuitry in an experience-dependent fashion and unveil potential therapeutic target for combating opioid abuse.